Pemanfaatan Chat GPT dalam Pembelajaran Bahasa Indonesia pada Materi Menulis Teks Laporan Hasil Observasi Kelas X SMA Negeri 1 Maumere - Mario Keviandro Emanuel Wetter; Trisnawaty Bura; Muhammad Lautama; Maria Ermilinda Dua Lering (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
Students' difficulty in producing Observation Report texts remains a major issue in Indonesian language learning. This condition has prompted teachers to utilize artificial intelligence technology, ChatGPT, as a learning aid. This study aims to describe the use of ChatGPT in Indonesian language learning in the subject of writing LHO texts. A qualitative approach was used at SMA Negeri 1 Maumere, with teachers and 10th grade students as the data sources. Data were collected through observation, interviews, and documentation, then analyzed using interactive analysis. The results of the study show that teachers and students understand the features and steps for using ChatGPT and demonstrate a positive attitude towards its application, such as awareness of the limitations of AI, responsible use, critical and evaluative attitudes, and understanding of the social impact of technology. The use of ChatGPT in learning involves three stages, namely pre-use (administrative preparation, understanding the concept of ChatGPT, and familiarization with the ethics of use), the use stage (initial, core, and final learning activities), and the evaluation stage of advantages and disadvantages. The weaknesses of ChatGPT include its inability to generate images, dependence on an internet connection, irrelevant search results, superficial answers, and limitations in understanding context. Its strengths include helping students understand LHO concepts, facilitating paragraph writing, and supporting topic selection and text structure development. These findings indicate that ChatGPT has the potential to serve as an effective tool in writing instruction, provided that it is used wisely and critically.